(untitled) (International Journal of Current Engineering and Technology, 2015)
The Fossil fuels such as gasoline and diesel fuel are the most central basis of energy for our society. The advantages of diesel engines are high fuel efficiency, reliability and durability. Use of biodiesel as an alternative to diesel could reduce the dependency on petroleum products and the pollution problem. Also fuel injection pressure plays vital role in the performance of engine. Injected fuel droplets get smaller as the injection pressure increases which contributes to better atomization of the fuel. Hence the effect of injection pressure on the performance of compression ignition engine fuelled with biodiesel and its blends with diesel is studied in this experimental study. Tests are conducted on CI engine fuelled with diesel to get base line data for comparing engine performance with various blends of Rice bran oil and diesel as test fuels at different injection pressures. The results indicate that the performance of engine is improved with R75 compared to other test fuels at different injection pressures. The BHP of R75 increases by 5.9 % at full load conditions when compared to Diesel. The brake specific fuel consumption with R 75 % decreases by 9 % as compared to diesel. Hence it can be concluded that the R 75 % can be used to increase the performance of the engine and without making any major changes to the engine hardware.